The impact of social media influencers on Vietnamese consumer’s purchase intention in the online travel area - Pham, Thanh Hai (2018)
Over the years, most developing countries have witnessed a significant growth of influence marketing (De Bruyn and Lilien, 2008). The influencer marketing is increasingly becoming an integral part of most marketing strategies in the APAC region, especially in Vietnam. Therefore, social media influencer is recognised as an essential information source which may impact travel purchase decision for Vietnamese users. However, the question of how social media influencers can impact consumer decision making is still new and debatable under the changing of the technology and economy. Driven by various theories in current research, this study tests a conceptual framework which examines which factors of social media influencers impact Vietnamese consumer purchase intention, including three conceptual constructs – trust, perceived value, and perceived risk by asking the following research questions: “What are the factors of social media influencers that affect the attitude of Vietnamese consumers about the travel brands, their products and services? How do these factors influence the purchase intention of Vietnamese consumers?”. The study extends the previous literature on social media and social media influencer by identifying specific determinants that can impact the intention of purchasing. Then, it collected data through an online survey involving 275 respondents who are social media users in Vietnam. Results from data analysis revealed that all three conceptual foundations – trust, perceived value and perceived risk had a significant influential effect on consumer intention of buying in the travel area. The findings suggested social media influencers to be a promising marketing strategy for increasing sales in the online tourism industry. The marketers should work closely with social media influencers to increase the perceived value and reduce the perceived risk of the content in social media influencers’ channel. Moreover, the marketing strategists should strive to emphasise the usefulness of consumer trust on social media influencers as a determinant in the long-term influence marketing strategy.